2018
DOI: 10.3982/ecta14525
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo Confidence Sets for Identified Sets

Abstract: It is generally difficult to know whether the parameters in nonlinear econometric models are point‐identified. We provide computationally attractive procedures to construct confidence sets (CSs) for identified sets of the full parameter vector and of subvectors in models defined through a likelihood or a vector of moment equalities or inequalities. The CSs are based on level sets of “optimal” criterion functions (such as likelihoods, optimally‐weighted or continuously‐updated GMM criterions). The level sets ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 69 publications
0
42
0
Order By: Relevance
“…In this section, we aim to discuss how our method practically compares to more standard methods using data from the Santa Clara study. In our comparison we include Bayesian methods, a classical likelihood ratio-based test, and the Monte Carlo-based approach to partial identification proposed by Chen et al (2018). 8…”
Section: Santa Clara Study: Comparison To Other Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we aim to discuss how our method practically compares to more standard methods using data from the Santa Clara study. In our comparison we include Bayesian methods, a classical likelihood ratio-based test, and the Monte Carlo-based approach to partial identification proposed by Chen et al (2018). 8…”
Section: Santa Clara Study: Comparison To Other Methodsmentioning
confidence: 99%
“…The parameter of interest in our application could only be the disease prevalence, whereas the true/false positive rates of the antibody test may be considered "nuisance". In this paper, we directly project Θ 1−α (or Θ alt 1−α ) on a single dimension to perform marginal inference (see Section 4), but this is generally conservative, especially at the boundary of the parameter space (Stoye, 2009;Kaido et al, 2019;Chen et al, 2018). A sharper way to do marginal inference with our procedures is an interesting direction for future work.…”
Section: Reject All Valuesmentioning
confidence: 99%
“…None of these establish uniform validity of confidence sets. Chen, Christensen, and Tamer () established uniform validity of MCMC‐based confidence intervals for projections, but aimed at covering the projection of the entire identified region ΘIfalse(Pfalse) (defined later) and not just of the true θ . Gafarov, Meier, and Montiel‐Olea () used our insight in the context of set identified spatial VARs.…”
Section: Introductionmentioning
confidence: 99%
“…For more discussion of the comparison among these options, see Kaido et al (2019a) and Gafarov (2019). Other alternatives include the procedures discussed by Romano & Shaikh (2008) and Chen et al (2018).…”
Section: Methodsmentioning
confidence: 99%
“…Romano & Shaikh (2008) discuss subvector inference based on subsampling. Chen et al (2018) discuss confidence sets for the identified set for subvectors based on a quasi-posterior Monte Carlo approach.…”
Section: Introductionmentioning
confidence: 99%